Women remembering the Prophet’s birthday: Maulid celebrations and religious emotions among the Alawiyin community in Palembang, Indonesia - Seise, Claudia (Azizah) (SEAS - Society for South-East Asian Studies, 2018)
In Palembang in South Sumatra, Indonesia, Maulid celebrations are considered an important religious event in the lives of many Muslims. Over the past twenty years, there has been an expansion of activities, the driving force behind which has been a young generation of Alawiyin in Palembang. Maulid celebrations organized by the Alawiyin in Palembang are separated along gender lines. In this paper, I show how female-only Maulid celebrations enable Muslim women, and especially the sharifat, to express their emotions and allow for bodily expressions during the actual Maulid event. I will argue that, in women-only celebrations, women express religious emotions which they wish to show but also which are expected from them as the expression of love for the Prophet Muhammad is part of the Islamic understanding internalized by the Alawiyin.